An Ultrasensitive Sandwiched Heterostructure Planar Photodetector with Gradient Quasi‐2D Perovskite. (22nd January 2023) - Pan, Yiyi; Wang, Haoliang; Wang, Yaxin; Wang, Yanyan; Li, Xiaoguo; Liu, Yiting; Deng, Liangliang; Liu, Kai; Hu, Tianxiang; Liu, Fengcai; Shi, Zejiao; Li, Chongyuan; et al.
Abstract: 2D Ruddlesden–Popper perovskites have attracted increasing attention for their outstanding optoelectronic properties and improved stability compared to the 3D counterparts. The unique nature of the crystal growth orientations and the uneven distribution in the 2D perovskites provide a great opportunity to construct a promising lateral photodetector device that has not been fully uncovered. Here, by improving the random orientation to the vertical orientation of the film in the lateral device structure, the dark current is expected to be significantly suppressed in the photodetector. Accompanied by the gradient phase distribution, a p‐type conductive channel at the bottom and another electron collection layer on the top are applied to achieve a high on/off ratio. Overall, the resultant photodetector realizes a low dark current of 10 −10 A and exhibits impressive photodetection performance, including a high responsivity of 10.10 A W −1, a notable detectivity of 6.83 × 10 12 Jones, and fast response speeds (14 ms/31 ms). Abstract : A lateral photodetector based on the PTAA/2D perovskite/C60 sandwich heterostructure, in which PTAA acts as the bottom conductive channel and C60 acts as an electron‐collection layer, is presented. Benefiting from the effective perpendicular charge transport and extraction, the photocurrent and responsivity of the device are greatly enhanced.